The Effect of Regulating Zoo Visitor-Penguin Interactions on Zoo Visitor Attitudes - Chiew, Samantha J.; Hemsworth, Paul H.; Sherwen, Sally L.; Melfi, Vicky; Coleman, Grahame J. (Frontiers in Psychology, 2019)
Understanding visitor attitudes towards zoo animals can inform the way zoos manage visitor-animal interactions, by identifying the factors that may influence visitors and the way visitors interact with animals. We investigated the relationship between visitor attitudes and penguin behavior and the effects of regulating visitor-penguin interactions on visitor attitudes and experience. Visitor attitudes towards little penguins (Eudyptula minor), their welfare, enclosure, visitor effects, enclosure manipulations and visitor experience at an Australian zoo were assessed. A 2×2 fully randomized factorial design was used to examine potential factors that may influence visitor attitudes: 1. Viewing proximity of visitors to the enclosure: ‘Normal viewing distance’ and ’Increased viewing distance’ and 2. Intensity of visitor behaviors: ‘Unregulated visitor behavior’ and ‘Regulated visitor behavior’. Visitor attitudes were assessed using an anonymous attitude questionnaire. Visitors were approached after they had finished viewing the penguins and were given two options to complete the questionnaire, either on an iPad on site during their zoo visit or online after their zoo visit. A total of 495 surveys (48% during zoo visit, 52% after zoo visit) were completed. Majority of respondents were non-zoo members, females and aged between 26-35 years old. Results revealed a significant relationship (p<0.05) between little penguin behavior and visitor attitudes where the more visible, active and close penguins were to the visitor viewing area, the more positive several visitor attitude scales were. In contrast, there were only a few treatment effects of regulating visitor viewing proximity and behavior on visitor attitudes in which attitudes towards ‘Positive penguin characteristics’ (p=0.024), ‘Neutral visitor effects’ (p=0.0023) and ‘Physical barriers’ (p=0.013) were affected. This suggests that physical barriers and/or signage are factors that influence visitor attitudes. However, it is unclear if the treatment effects influenced visitor attitudes directly, or if it was the changes in penguin behavior as a consequence of the treatments that were associated with visitor attitudes. These findings have increased our understanding of the multifaceted nature of visitor attitudes and have identified some possible influencing factors on attitudes that can be used to inform the way zoos manage visitor-penguin interactions, but clearly further research is required.